Implementasi Market Day dalam Menumbuhkan Karakter Kewirausahaan Siswa SD Negeri Ngadirejo 5 Kota Kediri - Eunike Rose Mita Lukiani; Shinta Maya Shafa (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
This study aims to examine the role of Market Day activities in fostering entrepreneurial character among students at SDN Ngadirejo 5, Kediri City. The background of this research stems from students’ strong determination to pursue a better future despite their parents’ economic limitations and the absence of practical entrepreneurship-based activities at the school. This study involved fifth-grade students, who were considered developmentally ready to engage in project-based learning. Using a qualitative approach with observations and interviews, the Market Day program was implemented through three stages: preparation, implementation, and evaluation. The findings show that Market Day effectively fosters key entrepreneurial character traits, including responsibility, empathy, self-confidence, critical reasoning, creativity, enthusiasm, adaptability, and persistence. Overall, Market Day provides a meaningful learning experience and serves as an effective innovation for developing entrepreneurial character from an early age.